PREVALENCE OF HYPOCALCEMIA DUE TO PHOTOTHERAPY IN NEWBORNS WITH NEONATAL JAUNDICE IN A TERTIARY CARE CENTER OF SOUTHERN RAJASTHAN - AISHWARYA GUPTA; RAJENDRA KUMAR SHARMA; MALVIA, SUNNY (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Neonatal jaundice is a prevalent condition affecting approximately 60–80% of newborns, with phototherapy being a widely utilized treatment. While double surface phototherapy (DSPT) offers enhanced efficacy, it has been associated with adverse effects, notably hypocalcemia. This study aims to determine the prevalence of hypocalcemia induced by DSPT in neonates with jaundice, identify risk factors, and evaluate clinical outcomes. Methods: This prospective observational study enrolled 200 neonates with jaundice undergoing DSPT in a tertiary neonatal intensive care unit. Baseline data, including gestational age, birth weight, and bilirubin levels, were recorded. Serum calcium levels were measured before initiating DSPT and at 24 and 48-h post-initiation. Statistical analysis was performed to identify risk factors associated with hypocalcemia. Results: Among 200 neonates, hypocalcemia prevalence increased from 6% at baseline to 38% at 24 h and 52% at 48 h post-DSPT. Symptomatic hypocalcemia occurred in 22% of affected neonates, with 0.9% experiencing seizures. Prematurity (<37 weeks), low birth weight (<2.5 kg), and high bilirubin levels (≥20 mg/dL) were identified as significant risk factors (p<0.05). Calcium supplementation normalized serum levels in all cases within 48 h, with no long-term complications observed during follow-up. Conclusion: DSPT is effective for treating neonatal jaundice but significantly increases hypocalcemia risk. Routine calcium monitoring and preventive supplementation protocols should be considered to minimize adverse outcomes.